PENGARUH INFLASI DAN TINGKAT PENGANGGURAN TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA - SEPTIATIN, AZIZ AZIZ; MAWARDI, MAWARDI MAWARDI; RIZKI, MUHAMMAD ADE KHAIRUR (I-Economics, 2016)
Macro economics is a study about activities of economy in a country. The indicator of macro economics are inflation, unemployment, and growth of economics. The aim of this research is to analyze. The factors which influence the growth of economics in Indonesia. The factors are inflation and growth of economics. This research using multiple regression method Ordinary Least Squares (OLS) which the data took from 2011 – 2015 per semester. Finally this research shows only unployment variable influence significantly to growth of economics with probability 0,0191. While the inflation show that the probability 0,1955. It means there is no influence significantly between inflation to growth economics.Key word: inflation, unemployment, growth of economics.